2020
DOI: 10.15252/embr.201948860
|View full text |Cite
|
Sign up to set email alerts
|

RNF 152 positively regulates TLR / IL ‐1R signaling by enhancing MyD88 oligomerization

Abstract: Toll‐like receptors (TLRs) are important pattern recognition receptors (PRRs) that are critical for the defense against invading pathogens. IL‐1β is an important pro‐inflammatory cytokine that also plays pivotal roles in shaping the adaptive immune response. TLRs and interleukin‐1 receptor (IL‐1R) share similar cytosolic domains and signaling processes. In this study, we identify the E3 ubiquitin ligase RNF152 as a positive regulator of TLR/IL‐1R‐mediated signaling. Overexpression of RNF152 potentiates IL‐1β‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Of note, a small fraction of GFP-RNF152 puncta do not colocalize with LAMP2 (white arrows in Figure 1C). This observation is consistent with a recent study indicating that RNF152 could also localize to endosomes (Xiong et al, 2020).…”
Section: Cycloheximide (Chx) Chase Screen To Determine the Half-livessupporting
confidence: 94%
See 1 more Smart Citation
“…Of note, a small fraction of GFP-RNF152 puncta do not colocalize with LAMP2 (white arrows in Figure 1C). This observation is consistent with a recent study indicating that RNF152 could also localize to endosomes (Xiong et al, 2020).…”
Section: Cycloheximide (Chx) Chase Screen To Determine the Half-livessupporting
confidence: 94%
“…Because a fraction of RNF152 localizes to the endosome (white arrows in Figure 1C, Xiong et al, 2020), it is possible that the observed degradation is due to the endosomal degradation of RNF152. To ensure that the lysosome population of RNF152 is fast-degrading, we performed the Lyso-IP experiment using cells collected before and after 2 hours of CHX treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the outlier window on BTA01 (at position: 17,740,000-19,640,000 bp), contained 6 protein coding genes including TMPRSS15 and CHODL, two genes that were reported to be under selection in the Iraqi indigenous cattle 13 . Similarly, the candidate region on the BTA24 (at position: 59,660,000-61,790,000 bp), harboured RNF152 gene which positively regulates Toll-like receptors (TLRs) which are important pattern recognition receptors that are critical for the defence against invading pathogens 36 . RNF152 gene was reported to be involved in local adaptations in the Ainu, a hunter-gatherer population of northern Japan 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The innate immune system senses invading pathogens by pattern recognition receptors that include the NOD-like receptors, RIG-like receptors, cytosolic DNA receptors, and TLRs [ 38 ]. TLRs recognize various microbial components, such as proteins, lipids, lipoproteins, nucleic acids, glycoproteins, leading to the activation of innate immune cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%